Шевченкові присвяти - Бондар, Л. (Слово і Час, 2009)
У статті розглядаються різні види Шевченкових присвят: присвяти-послання, присвяти-назви, дарчі
написи. Простежено історію їх функціонування (перенесення з одного твору до іншого, зняття присвят
тощо). Особлива увага приділена адресатам присвят і даті їх написання. Аналізується розгорнута
присвята як окремий жанр. This article explores different types of dedications used by T.Shevchenko, i.e. address dedications, title
dedications, and inscriptions serving as a sign of the writer’s respect for an addressee. The author of the
essay traces back how particular dedications were used, adopted in other inscriptions or removed. A particular
attention is paid to the addressees of T.Shevchenko’s dedications as well as to the exact dating of the latter.
Especially comprehensive dedications are treated here as a separate genre. В статье рассматриваются различные виды авторских
посвящений: посвящения-послания, посвящения-названия, дарственные надписи. Прослежено историю
их функционирования (перенос из одного произведения
в другое, снятие посвящений и пр.). Особенное внимание
уделено адресатам посвящений и датам их возникновения.
Анализируется развернутое посвящение как отдельный жанр.